2018
DOI: 10.4040/jkan.2018.48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aromatherapy on Stress Responses, Autonomic Nervous System Activity and Blood Pressure in the Patients Undergoing Coronary Angiography: A Non-Randomized Controlled Trial

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0)If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium. Purpose: The purpose of this study was to examine the effects of aromatherapy on stress responses, autonomic nervous system (ANS) activity, and blood pressure in patients hospitalized to receive corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The results in this study agree with the results of prior studies on aromatherapy examining the stress relief of coronary angiography patients [34] and the stress relief of nurses in specialized departments [16]. Furthermore, in studies on the general population, lavender has been found to enhance parasympathetic activity and have significant effects on stress relief and sleep [35].…”
Section: Discussionsupporting
confidence: 88%
“…The results in this study agree with the results of prior studies on aromatherapy examining the stress relief of coronary angiography patients [34] and the stress relief of nurses in specialized departments [16]. Furthermore, in studies on the general population, lavender has been found to enhance parasympathetic activity and have significant effects on stress relief and sleep [35].…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to our study, there was no statistically significant difference between the groups. That the mean systolic blood pressure and diastolic blood pressure scores in our study were found to be lower than those of Tüzün Özdemir’s [ 22 ] study is thought to be due to the effect of aromatherapy on hypertension associated with cardiovascular disease [ 30 32 ]. In parallel with the literature reviewed, patients in the control group in this study had significantly higher mean diastolic blood pressure after insulin injection [ 22 ].…”
Section: Discussioncontrasting
confidence: 82%
“…In a non-randomized study, aromatherapy with lavender, ylang-ylang, and neroli essential oils improved stress response, autonomic nervous system (ANS) function, and blood pressure in patients who underwent coronary angiography (29). The intervention group in the first treatment was given as an aromatic stone impregnated with 1 drop of a mixture of essential oils in a ratio of 4: 2: 1.…”
Section: Resultsmentioning
confidence: 99%